EVALUATION OF THE SCHOOL CATALYST PROGRAM IMPLEMENTATION - satiri, Satiri; Anriani, Nurul; Pahamzah, John; Muhyidin, Asep (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2024)
In education, the fundamental goal is to produce a generation that has competence and competitiveness. Syifa Fikriya Cikande Integrated Elementary School is an exemplary institution dedicated to this goal. Using a systematic and rigorous approach, the institution consistently strives to improve the quality and efficacy of its educational initiatives. This strategic evolution requires a thorough evaluation of the school's flagship program, which includes human resource empowerment, a paradigm shift in learning methodology, data-driven planning strategies, and comprehensive school digitization. As a pioneer in innovative pedagogical approaches, Syifa Fikriya Cikande Integrated Elementary School has systematically implemented a series of programs, each undergoing a careful evaluation process integrating quantitative and qualitative methodologies. It is an essential channel for continuous introspection and refinement in the scientific enterprise. Within the New Paradigm Learning environment, the institution achieved categorical compliance in providing pedagogical materials, reaching a 100% compliance rate. Moreover, adding new pedagogical paradigms, primarily through the judicious application of project-based learning methodologies, showed marked progress, indicating a considerable escalation from 60% to 95%. These developments underscore an unwavering commitment to developing a comprehensive educational environment to enhance the Pancasila Learner Profile.